Managing Technological Innovations at Deki Electronics - Shiv S. Tripathi; Sunil Ashra
Deki Electronics was a Noida based capacitor manufacturing firm. By virtue of being a technology-based manufacturing firm, it was susceptible to risks of technology obsolescence. The company got a major shock when the lighting industry shifted from CFL to LED-based lighting within a very short span of time. Innovation was the only key to their survival. The case explores how they learnt to manage technological innovations and explores the question that how to avoid such technological shocks.